Theory of International Economic Relations - Zelinska, Olena Z. (My University, 2022)
The study of discipline “Theory of International Economic Relations” implies acquaintance the students with the structure of Ukraine higher education system as well as key principles and mechanisms of the educational process arrangement by the Ukraine higher educational institutions in general and in particular by the Lesya Ukrainka Volyn National University. Students will navigate on expected types of undergraduate training for the whole period of study in International Economic Relations as well as on how to organize their learning process, taking into account the individual characteristics of the physical, mind and mental health, memory and so on. Also, students should develop an idea of international economic relations as an educational and scientific specialty as well as the international relations area, based on the theories of international trade and the international movement of factors since ancient times to the present.